Identification and Spatial Mapping of Termite Species Distribution in Oil Palm Plantations in Timpeh Subdistrict, Dharmasraya Regency, Indonesia - Alvin Niqmatull Akbar; Sri Heriza; Zahlul Ikhsan (Andalasian International Journal of Entomology, 2025)
Termites are one of the organisms that have the potential to reduce oil palm productivity, so it is necessary to identify the species and map their distribution to support more effective and sustainable management. This study was conducted to identify termite species and map their distribution in oil palm plantations in Timpeh District, Dharmasraya Regency, Indonesia. This study used a survey method with purposive sampling based on several criteria, including the presence of plant attack symptoms, air humidity ≥ 60%, the presence of rotten wood, the presence of termite nests, and the sampling location was selected in oil palm plantation areas located on the edge of local roads at a distance of about 0-15 meters. The termite samples obtained were identified morphologically using a microscope and identification keys. Termite distribution mapping was performed using ArcGIS 10.8 software, while the relationship between termite presence and environmental factors (temperature, light intensity, and humidity) was analyzed using Redundancy Analysis (RDA). The results showed that there were six termite species in Timpeh Subdistrict, namely Macrotermes gilvus, Coptotermes curvignathus, Pericapritermes mohri, Dicuspiditermes nemorosus, Nasutitermes longinasus, and Termes propinquus. The species M. gilvus has the widest distribution throughout the subdistrict and is not significantly influenced by environmental factors, but rather by its high adaptability. Meanwhile, the other species have a more limited distribution and tend to be influenced by factors such as humidity, light intensity, and the availability of organic material. The mapping results provide a crucial basis for determining priority areas for control and termite management strategies in oil palm plantations, enabling more effective and efficient approaches to be implemented.